2019
DOI: 10.3389/frobt.2019.00128
|View full text |Cite
|
Sign up to set email alerts
|

Task Dependent Group Coupling and Territorial Behavior on Large Tiled Displays

Abstract: Large display environments are highly suitable for immersive analytics. They provide enough space for effective co-located collaboration and allow users to immerse themselves in the data. To provide the best setting-in terms of visualization and interaction-for the collaborative analysis of a real-world task, we have to understand the group dynamics during the work on large displays. Among other things, we have to study, what effects different task conditions will have on user behavior. In this paper, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…We further also refer to prior work that has categorized degrees of interdependence in collaborative settings [e.g., tightly vs. loosely coupled, as also touched upon by Harris and Hancock (2019)]. For example, Sigitov et al (2019) have observed different user roles for tightly coupled collaborative work when interacting with a shared large display using mobile phones for interaction purposes. Similarly, different types of interdependence have been addressed for shared PC monitor (Tse et al, 2004), and co-located digital tabletops (Scott et al, 2003;Morris et al, 2004).…”
Section: Reflections On the Frameworkmentioning
confidence: 99%
“…We further also refer to prior work that has categorized degrees of interdependence in collaborative settings [e.g., tightly vs. loosely coupled, as also touched upon by Harris and Hancock (2019)]. For example, Sigitov et al (2019) have observed different user roles for tightly coupled collaborative work when interacting with a shared large display using mobile phones for interaction purposes. Similarly, different types of interdependence have been addressed for shared PC monitor (Tse et al, 2004), and co-located digital tabletops (Scott et al, 2003;Morris et al, 2004).…”
Section: Reflections On the Frameworkmentioning
confidence: 99%
“…Wallace et al [79] found a similar result using collaborative puzzle tasks, and moreover suggest that the user's range in front of the display can characterize degrees of collaboration. Finally, Sigitov et al [73] studied collaboration coupling and territoriality when pairs used a curved wall display. They suggest more types of territories than in previous works, on and in front of the wall display.…”
Section: Studies On Co-located Collaborationmentioning
confidence: 99%
“…The above works suggest that the situation is complex and that the space usage on the (virtual) displays and in the room depends on the collaborative strategies, the task, and the setup (e.g., tabletop vs. wall). Our setup is unique, we go beyond physical walls [7,35,48,73] Figure 2: Different virtual surfaces. On the left, an image of a typical virtual Surface with Cards.…”
Section: Studies On Co-located Collaborationmentioning
confidence: 99%